2018
DOI: 10.1016/j.athoracsur.2018.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diabetes Mellitus on Outcomes in Patients After Left Ventricular Assist Device Implantation

Abstract: Diabetic patients who underwent LVAD implantation had a higher risk of death compared with nondiabetic patients. Adverse event rates did not differ between the two groups. Finally, the degree of glycemic control in diabetic patients before LVAD was not found to influence mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Our study confirmed the importance of diabetes as a known risk factor for all types of infection. Previous studies have shown that the cumulative probability of death is higher in diabetic patients with LVADs, regardless of preoperative serum HbA 1 C concentration 15,16 . Similar to others, our study identified Staphylococcus as the most common organism in post‐LVAD infection 8,10,17 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study confirmed the importance of diabetes as a known risk factor for all types of infection. Previous studies have shown that the cumulative probability of death is higher in diabetic patients with LVADs, regardless of preoperative serum HbA 1 C concentration 15,16 . Similar to others, our study identified Staphylococcus as the most common organism in post‐LVAD infection 8,10,17 .…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that the cumulative probability of death is higher in diabetic patients with LVADs, regardless of preoperative serum HbA 1 C concentration. 15,16 Similar to others, our study identified Staphylococcus as the most common organism in post-LVAD infection. 8,10,17 Fungal and viral infections were also noted by others to comprise less than 10% of all infections.…”
Section: Prior Studiessupporting
confidence: 88%
“…The authors have added to the literature evidence that DM is associated with an increased rate of allcause mortality during continuous LVAD support. This retrospective analysis of 191 consecutive adult patients undergoing Heart Mate II LVAD as bridge to transplantation or destination therapy was performed from 2008 to 2014 (12). Although the study experienced all the usual limitations of a retrospective cohort design, including incomplete evaluation of the impact of type 1 versus type 2 DM, duration of DM, and treatment strategies, these realworld studies can provide valuable insight into optimal patient selection and management practices.…”
mentioning
confidence: 99%
“…Anyway, Usoh et al reported that despite no increased LVAD-associated complications in diabetic patients when compared with patients not suffering from diabetes, the occurrence of an initial complication (including infection, rehospitalization, or neurological dysfunction) led to higher mortality in the diabetic patient group (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation